2017
DOI: 10.1177/0363546517741306
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating In Vivo Articular Cartilage Repair by Tissue-Engineered Cartilage Grafts Produced From Auricular Chondrocytes

Abstract: This study proposes a feasible methodology to convert heterotopic auricular chondrocytes for articular cartilage repair, which may serve as potential alternative sources for cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Instead, both Safranin O (associated or not with the fast green dye for the bone compartment) and Toluidine Blue were the staining methods most frequently chosen for proteoglycans as well as glycosaminoglycans content, in addition to the Alcian Blue staining method. Only five studies utilized the two classical techniques to visualize collagen fibers in histological section, picrosrius red [35] or Goldner's trichrome [16, 18, 21, 30]. Finally, for undecalcified samples, the Stevenel Blue/Van Gieson Pichrofucsin dye [29], thionine staining [27], and Toluidine Blue were used to evaluate the osteochondral compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, both Safranin O (associated or not with the fast green dye for the bone compartment) and Toluidine Blue were the staining methods most frequently chosen for proteoglycans as well as glycosaminoglycans content, in addition to the Alcian Blue staining method. Only five studies utilized the two classical techniques to visualize collagen fibers in histological section, picrosrius red [35] or Goldner's trichrome [16, 18, 21, 30]. Finally, for undecalcified samples, the Stevenel Blue/Van Gieson Pichrofucsin dye [29], thionine staining [27], and Toluidine Blue were used to evaluate the osteochondral compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Cell plasticity is a key feature of stem/progenitor cells that is regulated by the environment of the surrounding tissue (MacLean et al 2017; Wong et al 2018). After transplantation, cellular differentiation and incorporation with host tissues are important to constitute functional histologic units.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen hydrogels reduce the risk of immune rejection by stimulating the ECM formation, reduce immunogenicity of exogenous cells that are seeded in engineered hydrogel constructs and promote cartilage regeneration [ 99 ]. In addition, Wong et al found that type II collagen was capable of converting auricular chondrocytes into articular cartilage after dedifferentiation by monolayer passaging [ 100 ]. By using type I collagen as scaffold combined with stromal cell-derived factors-1 (SDF-1) as growth factor, Zhang et al successfully induced the migration and adhesion of C-MSCs and SM-MSCs and promoted the self-repair of partial thickness defects [ 30 ].…”
Section: Current State-of-art Of Hydrogels Designed For Cartilage Regmentioning
confidence: 99%